Analysis of Consumer Dependence in Confessions of Shopaholic by Sophie Kinsella - Trisnasari Wahyu Prinanintyas; Prayudias Margawati (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
Human needs are essential for mental well-being and determining the direction in life. Failure to meet these needs may result in individuals experiencing emotional instability, identity confusion, and internal conflict. Sophie Kinsella's novel Confessions of a Shopaholic illustrates this dilemma through the character Rebecca Bloomwood, whose compulsive purchasing transcends mere lifestyle; it signifies deeper mental health concerns. The objective of this study is to examine the psychological challenges encountered by the main character and how her behavior is influenced by unfulfilled needs, particularly those pertaining to self-esteem and belongingness. This research employs a qualitative methodology grounded in psychological literacy critique and Abraham Maslow's hierarchy of needs theory. An in-depth examination and textual analysis of the argument reveals that Rebecca Bloomwood undergoes two significant psychological phases: the emotional turmoil phase, characterized by unmet wants, and the nascent self-awareness phase, during which she tries to take charge of her life again. The character’s journey shows that psychological needs must be met from the inside, not the outside. Rebecca’s story shows how hard it is to live in a culture where appearances and social standing can change who you are.